Unlocking Vocabulary Potential: Student Perceptions of Wordwall Games - Zulfa, Femi Munatuz; Suminar, Anne Ratna; Setiawati, Pipih (Universitas Pahlawan Tuanku Tambusai, 2026)
While existing research on Wordwall frequently prioritizes pedagogical perspectives or quantitative test outcomes, the subjective experiences of learners remain underexplored. This qualitative descriptive study investigates how Indonesian English as a Foreign Language (EFL) young learners perceive and experience Wordwall gamification within the vocabulary learning process. Employing a qualitative descriptive method, data were collected through classroom observations and semi-structured interviews with six eighth-grade students in Garut. The findings indicate that learners demonstrated a strong understanding of the platform, resulting in increased motivation and active participation. Observational data confirm that students exhibit higher focus and collaboration during gameplay compared to traditional sessions. Despite minor technical constraints, this study concludes that Wordwall successfully fosters an engaging, technology-supported learning environment aligned with the Merdeka Curriculum goals.